Rebranding Agrowisata Kebun Herbal Kesuma Bangsa Menjadi Eduagrowisata Ramah Keluarga - Feti Arman; Dwi Agus Riyanto; Taufik Rahman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Limited equipment and limited skills are hindering the promotion of the Kesuma Bangsa Herbal Garden Agrotourism. Lack of knowledge of modern production techniques and efficient practices leads to low capacity. Furthermore, inconsistent quality is a challenge due to inefficient introduction and marketing. The lack of a clear and measurable business plan, particularly in terms of manual financial record-keeping, poses a risk of errors in cash management, which ultimately negatively impacts business sustainability. Limited knowledge of marketing and promotion, limited access to markets and distribution networks, and less than optimal use of digital marketing methods. Consequently, the Kesuma Bangsa Herbal Garden Agrotourism market access is limited. Through this community service, the Kesuma Bangsa Herbal Garden Agrotourism market will be expanded not only locally but also nationally. The Kesuma Bangsa Herbal Garden Agrotourism still faces limitations in digital marketing, particularly in understanding information technology that can be used to improve its business. This limitation impacts partners' lack of digital marketing skills. The Kesuma Bangsa Herbal Garden Agrotourism product lacks a clear branding strategy to differentiate its products in the market. This makes it difficult for the business to grow and compete, especially with other MSMEs that already have their own unique offerings. The problem formulation must be stated concretely and clearly in the introduction. Explain the objectives to be achieved through the community service activities with measurable and realistic targets. Also outline the expected benefits of the community service activities for both the target audience and the development of knowledge.